Gas-liquid two-phase flows in double inlet cyclones for natural gas separation. Issue 1 (1st January 2017) - Yang, Yan; Wang, Shuli; Wen, Chuang
Abstract: The gas-liquid two-phase flow within a double inlet cyclone for natural gas separation was numerically simulated using the discrete phase model. The numerical approach was validated with the experimental data, and the comparison results agreed well with each other. The simulation results showed that the strong swirling flow produced a high centrifugal force to remove the particles from the gas mixture. The larger particles moved downward on the internal surface and were removed due to the outer vortex near the wall. Most of the tiny particles went into the inner vortex zones and escaped from the up-outlet. The swirling flow was concentric due to the design of the double inlet for the cyclonic separator, which greatly improved the separating efficiency. The separating efficiency was greater than 90% with the particle diameter of more than 100 μm.